Adaptive management in socio-ecological systems: A case study of camedor palms (Chamaedorea quezalteca) in La Sepultura Biosphere Reserve, Chiapas, Mexico - Jiménez-Jiménez, Viridiana (2022)
[Introduction]: Studies on adaptive management in socio-ecological systems recognize that natural resources (e.g., forests) are not isolated, but are interwoven in their ecosystems with social, institutional, economic, and political components. This study addresses adaptive management based on the use of the camedor palm (Chamaedorea quezalteca), in the La Sepultura Biosphere Reserve (RIBESE), Chiapas, Mexico. The camedor palm resource is considered the most used non-timber forest product (NTFP) by rural and indigenous communities in Central America. The contribution of the study goes beyond the ecological aspects of the palm, it was approached as a complex and dynamic socio-ecological system (SES). [Objective]: To analyze the management of camedor palms through an analysis of the adaptive renewal cycle of SSE. [Methodology]: Semi-structured interviews were applied to key actors, a participatory workshop with palm producers, and the empirical application of the adaptive cycle model proposed by Holling. [Results]: Three stages represented by adaptive cycles were identified: 1) an unregulated exploitation of wild palm populations (1960-2004); 2) regulation and local participation in the management and conservation of palms (2005-2014); and 3) co-management and community reorganization for the sustainable use of palms (2015-2020). [Conclusion]: The evolutionary and adaptive process of the SES has been influenced by intrinsic changes in community development and by external factors, such as the international palm market, public policies, conservation and development programs, and the interaction of governmental and non-governmental actors.